Peramalan Kebutuhan Bahan Baku Plat Besi Menggunakan Metode Runtun Waktu Autoregressive Integrated Moving Average (ARIMA) dan Meminimumkan Biaya Total Persediaan dari Hasil Peramalan Mengunakan Metode Period Order Quantity (POQ) - Mulyta Anggraini; Rito Goejantoro; Yuki Novia Nasution (EKSPONENSIAL, 2019)
ARIMA method is used to predict future patterns of data that is expected to approach the actual data. In the case of inventory control, the company must have a good planning system for forecasting results to get maximum benefit. Period Order Quantity Method is used to solve inventory problem and minimize the total inventory cost. The research objective are to predict how many iron plates which CV. Isakutama needs from January 2017 to Desember 2017 with ARIMA method and to minimize the predicted total inventory cost using Period Order Quantity method. Based on the research, the forecasting results of the iron plates for 12 months are 24, 24, 25, 24, 25, 25, 25, 25, 25, 25, 25 and 25 units, so that the total inventory cost is Rp.1,177,264,000 by providing them once every 52 days.